2004
DOI: 10.1093/ajcn/80.4.1012
|View full text |Cite|
|
Sign up to set email alerts
|

Olive oil, the Mediterranean diet, and arterial blood pressure: the Greek European Prospective Investigation into Cancer and Nutrition (EPIC) study

Abstract: Adherence to the Mediterranean diet is inversely associated with arterial blood pressure, even though a beneficial component of the Mediterranean diet score-cereal intake-is positively associated with arterial blood pressure. Olive oil intake, per se, is inversely associated with both systolic and diastolic blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
319
4
24

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(362 citation statements)
references
References 46 publications
15
319
4
24
Order By: Relevance
“…A suggestion for a lower effect of plant-food consumption on BP when monounsaturated fatty acid (MUFA) intake was high was previously reported by our group in a cross-sectional assessment of a Mediterranean population (Alonso et al, 2004b). On the other hand, the European Prospective Investigation into Cancer and NutritionGreece group (Psaltopoulou et al, 2004) reported that an inverse association between vegetable consumption and systolic blood pressure (SBP) was lost when the estimate was adjusted for olive oil consumption.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…A suggestion for a lower effect of plant-food consumption on BP when monounsaturated fatty acid (MUFA) intake was high was previously reported by our group in a cross-sectional assessment of a Mediterranean population (Alonso et al, 2004b). On the other hand, the European Prospective Investigation into Cancer and NutritionGreece group (Psaltopoulou et al, 2004) reported that an inverse association between vegetable consumption and systolic blood pressure (SBP) was lost when the estimate was adjusted for olive oil consumption.…”
Section: Introductionmentioning
confidence: 71%
“…The role of diet seems essential in the prevention of hypertension (Appel et al, 2006). Dietary trials (Appel et al, 1997;John et al, 2002) and observational studies (Psaltopoulou et al, 2004) have provided evidence to support the effectiveness of increasing the consumption of plant foods (especially vegetables and fruits) to decrease the risk of developing hypertension. Olive oil (Ferrara et al, 2000;Perona et al, 2004;Covas et al, 2006;Estruch et al, 2006) has been also suggested as an effective means to reduce blood pressure (BP) levels among hypertensives and to prevent the incidence of hypertension among normotensives (Alonso and Martinez-Gonzalez, 2004a;Perez-Jimenez et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Values of 0 or 1 were assigned to each of the eight indicated components by using the respective sexspecific medians as cutoffs (Trichopoulou et al, 2003;Psaltopoulou et al, 2004). For beneficial components (vegetables, legumes, fruits, cereals, olive oil and fish), participants whose consumption was below the median were assigned a value of 0, whereas participants whose consumption was at or above the median were assigned a value of 1.…”
Section: Mediterranean Dietary Patternmentioning
confidence: 99%
“…A clear example of a healthy dietary pattern is the 'traditional' Mediterranean diet, which has been shown to be protective against mortality for several causes and the development of coronary heart disease, stroke, hypertension and other chronic diseases (Martinez-Gonzalez et al, 2002;Psaltopoulou et al, 2004;Sanchez-Villegas et al, 2005;Trichopoulou et al, 2005). The nutritional objectives for the Spanish population are therefore based in the development of dietary guidelines within a Mediterranean context (Serra-Majem and Aranceta, 2001).…”
Section: Introductionmentioning
confidence: 99%